Utilization of Scenedesmus obliquus for green liquid hydrocarbons production using ultrasonic and catalytic upgrading technologies - Ido, Alexander L.; De Luna, Mark Daniel G.; Capareda, Sergio C. (Quezon City College of Engineering, University of the Philippines Diliman, 2016)
The quest for liquid biofuels to supplement petroleum-based fuel has been currently focused on finding non-food biomass as a biofuel feedstock. Scenedesmus obliquus microalgae is a promising candidate as biofuel feedstock characterized by its distinctive qualities like high lipid content and productivity, shorter harvest time, and capability of bioremediation when grown in wastewater. This work investigated the applicability of S. obliquus as feedstock for producing liquid hydrocarbons within gasoline and diesel-range via two-stage process: Ultrasonic Assisted Solvent Extraction (UASE) and catalytic upgrading. Important parameters in UASE, namely resonance amplitude (40-80 um), HIP ratio (1-5 v/v) and reaction time (30-110 min) were optimized using response surface methodology with respect to lipid yield. The extracted lipid or oil was then catalytically upgraded over a synthesized 20 wt percent Ni/C solid catalyst by varying the reaction temperature (150-350 degree celsius), dodecane to oil mass ratio (2-6 w/w) and hydrogen pressure (1-5 Mpa). Results on the optimization of lipid yield from S. obliquus via UASE demonstrated a yield of 26.63 percent comparable or even better to other feedstocks. Extracted oil had a heating value of 35.38 MJ/kg, higher than those produced by pyrolysis (29 MJ/kg) and liquefied DME bio-oil (33.8 MJ/kg. FTIR and GCMS analyses of UASE extracted lipid showed an abundance of saturated fatty acids of 79.38 percent making the route promising for large-scale lipid production in the biofuel industry. Catalytic upgrading of S. obliquus oil significantly reduced the percentage of undesirable oxygen and nitrogen and completely removed the unwanted sulfur. The resulting high-quality product has a heating value of 43.78 MJ/kg, comparable to petroleum diesel. Produced liquid products mainly composed of 95.35 percent alkanes and 5.65 percent alkenes. This study has demonstrated the attractiveness of S. obliquus as a biofuel feedstock. It also revealed that the two-stage process, namely UASE of S. obliquus microalgae and the subsequent catalytic upgrading of the extracted oil can produce green gasoline and green diesel, bearing significant contribution in the field of biofuel production.
Thesis (Ph.D. Environmental Engineering)--University of the Philippines Diliman
Keywords: Green algae; Microalgae -- Biotechnology; Biomass chemicals